Bipolar Disorder in a Patient with VACTERL Syndrome: A Case Report - Parikh, Parinda; Mathew, Namitha Maria; Dadem, Ananya Reddy; Manepalli, Sahia; Narravula, Rithika; Wubuli, Dilinuer; Suthar, Himani J; Singh, Shaurya Kumar; Lee, Eunsaem; Chandra-Kaushik, Arushi; et al. (International Journal of Innovative Research in Medical Science, 2025)
VACTERL association is a non-random constellation of congenital anomalies, typically involving at least three of the following systems: vertebral defects, anal atresia, cardiac malformations, tracheoesophageal fistula, renal anomalies, and limb abnormalities. While defined by structural defects, emerging evidence suggests increased rates of correlations with neurodevelopmental and psychiatric conditions. Bipolar disorder is a chronic mood disorder marked by recurrent episodes of mania or hypomania and depression, with pathophysiology involving fronto-limbic dysregulation, neurotransmitter imbalance, neuroinflammation, mitochondrial dysfunction, and impaired neuroplasticity. We report a case of Bipolar I Disorder in a 21-year-old man with VACTERL association (vertebral anomalies, anal atresia, cardiac defects, tracheoesophageal fistula) and normal cognitive development. He presented with a two-week manic episode with psychotic features and responded well to lithium and olanzapine. To our knowledge, this is the first case reported a potential link between VACTERL association and a bipolar disorder. This case highlights the need for increased awareness of possible psychiatric comorbidities in patients with complex congenital anomalities and underscores the importance of incorporating neuropsychiatric screening into VACTERL patient care.